2019
DOI: 10.3389/fneur.2019.00928
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Dysfunction on Multifocal Electroretinography May Help Differentiating Multiple Sclerosis From Neuromyelitis Optica Spectrum Disorder

Abstract: Purpose: To evaluate the intermediate and outer retina of patients with multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) using OCT and multifocal electroretinography (mf-ERG). Methods: Patients with MS ( n = 30), NMOSD ( n = 30), and healthy controls ( n = 29) underwent visual field (VF), OCT, and mf-ERG testing. The eyes were distributed into 5 groups: MS with or without history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 46 publications
(58 reference statements)
1
23
4
Order By: Relevance
“…How, then, can we interpret the findings of Filgueiras et al (1) suggesting supernormal bipolar function in MS patients in the light of this pre-existing literature, and are there any factors which may account for this apparent discrepancy? In attempting to reconcile their findings with previous work from our group (8), Filgueiras suggested that our findings may be less reliable due to the use of manufacturers' normative databases from our electrophysiology device for comparison, rather than control data acquired on-site using the same conditions as for our patient cohort.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…How, then, can we interpret the findings of Filgueiras et al (1) suggesting supernormal bipolar function in MS patients in the light of this pre-existing literature, and are there any factors which may account for this apparent discrepancy? In attempting to reconcile their findings with previous work from our group (8), Filgueiras suggested that our findings may be less reliable due to the use of manufacturers' normative databases from our electrophysiology device for comparison, rather than control data acquired on-site using the same conditions as for our patient cohort.…”
mentioning
confidence: 93%
“…These differences included the MF-ERG waveform components and retinal areas analyzed. The exclusion of R5 from analysis by Filgueiras et al (1), in order to facilitate comparison with perimetric data, may be particularly relevant given that we recorded R5 P1 peak times which were significantly delayed in MS patients relative to normative data (8). The analysis of different retinal areas makes it challenging to compare the results of the two studies directly.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…However, the few papers that have investigated the potential of mfERG analysis for diagnosing MS are based on traditional analysis of amplitudes and latencies and have produced conflicting findings [7,[15][16][17][18][19][20], perhaps because of the heterogeneity of the subjects analyzed (different types of MS and presence/absence of ON) and the use of different mfERG technologies.…”
Section: Introductionmentioning
confidence: 99%